Kajian Hukum Pencemaran Udara DKI Jakarta ditinjau Perbandingan Hukum Lingkungan Hidup Indonesia, Malaysia, dan Singapura - Wahyu Donri Tinambunan; Reviansyah Erlianto (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
The progress of science and technology in Indonesia has an impact on several acts of environmental destruction, one of which is in DKI Jakarta. The need for management and control of all actions whose implementation has an impact on the balance of nature in accordance with environmental regulations. However, in its application it is still found that the actions taken are not appropriate and do not pay attention to the impact on the balance of nature. Where the purpose of the study is to determine the role of the state in environmental protection, and to compare the actions of air pollution in terms of the laws and regulations of Indonesia, Malaysia, and Singapore. The normative legal research method collected through literature study is in the form of secondary data, and the author makes a legal comparison between Indonesia, Malaysia, and Singapore. The results obtained, that all forms of environmental management and utilization must pay attention to the impact on nature, the three countries have implemented environmental regulations that are oriented towards environmental sustainability and balance.